OP09 Long-term Colectomy rates of Ulcerative Colitis over 40-year of Different Therapeutic eras – Results from a Western Hungarian Population-based Inception Cohort between 1977–2020. (30th January 2023) - Lakatos PhD, P L; Gonczi, L; Lakatos, L; Golovics, P A; Pandur, T; David, G; Erdelyi, Z; Szita, I
Abstract: Background: Few population-based studies have investigated the long-term colectomy rates of ulcerative colitis (UC). The present study is a continuation of the Veszprem IBD population based cohort with a follow-up of the incidence and disease course for over 40 years. We aimed to assess the colectomy rates over 40 years of different therapeutic eras in a prospective population-based inception cohort from Veszprem Province, Western Hungary. Methods: Patient inclusion lasted between January1, 1977 and December31, 2018. Patient follow-up ended December 31, 2020. Both in-hospital and outpatient records were collected and comprehensively reviewed at diagnosis and during clinical follow-up. Disease extension was evaluated based on the Montreal classification. Colectomy rates and disease course were examined in three different eras based on the time of UC diagnosis; cohort-A(1977-1995), cohort-B(1996-2008), and cohort C(2009-2018). Results: Data of 1, 370 incident UC patients were analyzed (male/female: 702/668; median age at diagnosis: 37 years(y) [IQR: 26-51]), with a median of 17y (IQR 9-24) follow-up. Table 1. The overall colectomy rate was 76/1, 370 patients during the total follow-up. The proportion of extensive colitis at diagnosis increased over time (24.2% / 24.3% / 34.9% in cohorts A/B/C; p=0.001). Overall immunosuppressive therapy exposure was increasing in the cohorts (11.3% / 20.9% / 34.4%; p<0.001), as well as the probability of biological therapy initiation within 5 years of diagnosis (0.0±0% / 3.3±0.7% / 13.9±1.8%; pLogRank<0.001). Figure 1 . There was no significant difference in the cumulative probability of proximal disease progression from proctitis (E1) to left-sided colitis/extensive colitis (E2/E3) or from left-sided colitis (E2) to extensive colitis (E3) over time in cohorts A, B, and C (Long-rank=0.482). Figure 2. The cumulative probability of colectomy in the total population was 4.1±0.6% after 10 years, 6.3±0.8% after 20 years, and 8.8±1.2% after 30 years. There were no statistically significant differences in the cumulative probability of colectomies between cohorts A/B/C: 1.7±0.7% / 2.2±0.6% / 3.7±1.0% after 5 years; 3.5±1.0% / 3.9±0.8% / 4.5±1.2% after 10 years; and 6.9±1.4% / 5.3±1.0% (cohorts A/B) after 20 years [pLogRank=0.447]. Figure 3. Extensive disease (HR 2.3;95%CI 21.60-3.37) and continuous uncontrolled disease activity (HR 6.89;95%CI 4.15-11.46) were independent predictors for colectomy. Table 2. Conclusion: No differences in proximal disease progression and colectomy rates have been observed in the incident UC patients over 40 years despite increasing use of immunomodulators and biological therapies.